2019
DOI: 10.1186/s12864-019-5857-0
|View full text |Cite
|
Sign up to set email alerts
|

De novo sequencing of tree peony (Paeonia suffruticosa) transcriptome to identify critical genes involved in flowering and floral organ development

Abstract: Background Tree peony ( Paeonia suffruticosa Andrews) is a globally famous ornamental flower, with large and colorful flowers and abundant flower types. However, a relatively short and uniform flowering period hinders the applications and production of ornamental tree peony. Unfortunately, the molecular mechanism of regulating flowering time and floral organ development in tree peony has yet to be elucidated. Because of the absence of genomic information, 454-based trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…In this study, N50 was 1,780 bp, indicating a good assembly. The average length of measured sequence obtained was 1,189 bp, which was higher than that of other tree peony researches [8,17], Syringa oblata (853 bp) [23], flowering Chinese cabbage (779 bp) [24], and bamboo (736 bp) [25]. After assembly, a total of 86,195 unigenes were obtained, among which 49, 172 were annotated into the NR database.…”
Section: Transcriptome Sequencing Assembly and Functional Annotationmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, N50 was 1,780 bp, indicating a good assembly. The average length of measured sequence obtained was 1,189 bp, which was higher than that of other tree peony researches [8,17], Syringa oblata (853 bp) [23], flowering Chinese cabbage (779 bp) [24], and bamboo (736 bp) [25]. After assembly, a total of 86,195 unigenes were obtained, among which 49, 172 were annotated into the NR database.…”
Section: Transcriptome Sequencing Assembly and Functional Annotationmentioning
confidence: 89%
“…A total of 29,275 unigenes were obtained from the bud transcriptome of tree peony. Among the DEGs, 64 flowering-related genes, and the genes of PsAP1, PsCOL1, PsCRY1, PsCRY2, PsFT, PsLFY, PsLHY, PsGI, PsSOC1, and PsVIN3 probably regulated reblooming [8]. A large number of DEGs on the transcriptome data of tree peony (P. ostii) seeds were related to oil biosynthesis and fatty acid metabolism [9].…”
mentioning
confidence: 99%
“…Certainly, studying the complete genome is necessary to gain a comprehensive understanding of the gene network involved in flowering. Utilizing powerful genetic tools based on next generation sequencing are an effective strategy for studying complex gene networks in flowering [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, researchers are widely using transcriptomics and other powerful genetic tools based on next generation sequencing to study complex gene networks involved in flowering. These studies provide a comprehensive understanding of the gene network involved in flowering of model and nonmodel plants [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Roche/454 sequencing was used to understand the pistillate flowering in Carya cathayensis, which found that the flowering event of pistillate flower buds in hickory was triggered by several pathways synchronously, including GA pathway [6]. Using reblooming, non-re-blooming, and wild-type tree peonies (Paeonia suffruticosa), Wang et al pointed that PsGID1 was important GA signaling genes, and suggested that GA pathway played an important role in the flowering regulation of tree peony [7]. Similar research results were also found in Populus L. [8], Prunus mume [9], Poncirus trifoliata [10] and other woody plants.…”
mentioning
confidence: 99%